Evaluation of the passivity limits in austenitic stainless steel exposed to H2S-containing brines using point defect model analysis. (17th February 2022) - Case, Raymundo
ABSTRACT: This study evaluates the effects of temperature, H2 S, and Cl − concentration on the onset of localized corrosion, in UNS S31603 stainless steel by evaluating the changes in the behavior of the passive layer. This is accomplished experimentally by using direct current electrochemical methods to study the passive layer formed by the stainless steel, in equilibrium with a gas phase at 2.8 MPa (400 psi) containing up to 60% mol of H2 S (bal. CO2 ) at temperatures up to 150°C. The results indicate that the increase in the likelihood of both metastable and stable pitting on the stainless steel is consistent with the increase in the metal cation diffusivity as postulated by the point defect theory. In this context, the solution temperature was found to exert a larger effect than the H2 S activity.